2019
DOI: 10.22270/jddt.v9i1-s.2284
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Some New Rhodanine Analogues as Aldose Reductase Inhibitors (ARIs)

Abstract: Diabetes mellitus is a metabolic disorder characterized by hyperglycemia resulting long-term secondary complication. Aldose reductase, the rate-limiting enzyme of the polyol pathway, plays a key role in the treatment of diabetic complications. Appropriately, inhibition of this enzyme is emerging as a major therapeutic strategy for the pathogenesis of secondary complication. In this study, we describe a series of 5 aryl benzylidene -thiazolidine, 4-dione derivatives, F3 synthesized as aldose reductase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…reported a series of 5‐arylbenzylidene‐2,4‐dioxathiazolidines were synthesized and biologically assessed for AR inhibitory property and hypoglycaemic activity. Compound 109 showed potent AR inhibition activity with 83.14 % as compared to standard sorbinil 70.2 % and further series were assessed in‐vivo for their hypoglycaemic potential against Wistar rats, electron‐withdrawing group like No 2 and rhodanine at 3‐position of phenyl containing compound 110 shown to induce the greatest reduction in BGL with 131.11±1.59 mg/dL as compared to standard rosiglitazone 135±1.185 mg/dL [120] . Singh V et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported a series of 5‐arylbenzylidene‐2,4‐dioxathiazolidines were synthesized and biologically assessed for AR inhibitory property and hypoglycaemic activity. Compound 109 showed potent AR inhibition activity with 83.14 % as compared to standard sorbinil 70.2 % and further series were assessed in‐vivo for their hypoglycaemic potential against Wistar rats, electron‐withdrawing group like No 2 and rhodanine at 3‐position of phenyl containing compound 110 shown to induce the greatest reduction in BGL with 131.11±1.59 mg/dL as compared to standard rosiglitazone 135±1.185 mg/dL [120] . Singh V et al.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 109 showed potent AR inhibition activity with 83.14 % as compared to standard sorbinil 70.2 % and further series were assessed in-vivo for their hypoglycaemic potential against Wistar rats, electron-withdrawing group like No 2 and rhodanine at 3-position of phenyl containing compound 110 shown to induce the greatest reduction in BGL with 131.11 � 1.59 mg/dL as compared to standard rosiglitazone 135 � 1.185 mg/dL. [120] Singh V et al reported benzoxazolyl linked rhodanine and their cycle analogues were synthesized and screened for their αamyloglucosidase inhibitory potential activity. Benzoxazole compound 111 exhibited potent α-amyloglucoridase inhibition with IC 50 : 0.24 � 0.01 μM as compared to standard acarbose with IC 50 : 15.01 � 1.09 μM and hydrogen bond formation between carbonyl group of rhodanine and with LYS1460 amino acid in binding pocket.…”
Section: Synthetic Routes For Rhodanine Derivativesmentioning
confidence: 99%